2008
DOI: 10.1111/j.1600-065x.2008.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

How the study of children with rheumatic diseases identified interferon‐α and interleukin‐1 as novel therapeutic targets

Abstract: Our studies in children with rheumatic diseases have led to the identification of two of the oldest cytokines, type I Interferon (IFN) and Interleukin 1 (IL-1), as important pathogenic players in Systemic Lupus Erythematosus (SLE) and Systemic onset Juvenile Arthritis (SoJIA) respectively. These findings were obtained by studying the transcriptional profiles of patient blood cells and by assessing the biological and transcriptional effect(s) of active patient sera on healthy blood cells. We also identified a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 177 publications
(199 reference statements)
0
37
0
1
Order By: Relevance
“…The extent of the increase in IFNα production has a strong correlation with the stages of the disease [12]. These findings implicate the pivotal role of IFNα in the pathogenesis of SLE, leading to the development of IFN-related antagonists as a potential therapeutic intervention in SLE [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…The extent of the increase in IFNα production has a strong correlation with the stages of the disease [12]. These findings implicate the pivotal role of IFNα in the pathogenesis of SLE, leading to the development of IFN-related antagonists as a potential therapeutic intervention in SLE [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been reported that members of IL-1 family, namely IL-1b,IL-1 receptor antagonist (IL-1Ra) and IL-18, appear to be closely associated with the development and course of SLE [7,20,21], in present study, we investigated whether abnormal serum IL-33 level was closely associated with development of SLE in Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested that SoJIA might be linked to abnormalities in the innate immune system [43,44]. SoJIA is typically considered a polygenic disease, and candidate-gene association studies reported many risk alleles.…”
Section: January 2015: Monogenic Form Of Systemic Juvenile Idiopathicmentioning
confidence: 99%